(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2014)
The present study describes the development and validation of an in vitro dissolution method for evaluation to release diclofenac potassium in oral suspension. The dissolution test was developed and validated according to international guidelines. Parameters like linearity, specificity, precision and accuracy were evaluated, as well as the influence of rotation speed and surfactant concentration on the medium. After selecting the best conditions, the method was validated using apparatus 2 (paddle), 50-rpm rotation speed, 900 mL of water with 0.3% sodium lauryl sulfate (SLS) as dissolution medium at 37.0 ± 0.5°C. Samples were analyzed using the HPLC-UV (PDA) method. The results obtained were satisfactory for the parameters evaluated. The method developed may be useful in routine quality control for pharmaceutical industries that produce oral suspensions containing diclofenac potassium.